Analisis Resepsi Penonton Mengenai Isu Kesehatan Mental pada Film “Sleep Call” - Fadhilah Samudra Arsy; Windri Saifuddin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research wants to see how adult audiences accept the movie “Sleep Call” on mental health issues. Film is one of the important mass communication media to tell events or social issues that occur in everyday life. the purpose of this study is to determine the adult audience's acceptance of mental health issues in the film ''Sleep Call''. This research is a type of descriptive qualitative research. This research is specifically more directed at using the reception analysis method, this aims to answer the question of how the audience in this study receives a message from the media and is interpreted based on different backgrounds, social, and culture.